Pedagogical Pragmatism: A New Critical Approach to the Development of Resources for Learning - Roberts, George; Huggins, Richard (Proceedings of the International Conference on Networked Learning, 2004)
In this paper we put forward three inventories of good design practice. We then overlay these with a model, which we call pedagogical pragmatism, that uses a metaphor of the body: stance, face and posture, to articulate the principles we believe need to be attended to by a designer for learning. In respect of stance, the designer must first attend to the channel of communication then the relationships between the people involved before dealing with the content or subject of the course. In respect of face, the designer should address their own beliefs about learning because it is with these beliefs that learning relationships will be negotiated. Finally in respect of posture the designer will be aware not only of the recipients of the design, i.e. the putative, “ideal” learner, but also of an array of referees, or stakeholders, which might include funding bodies, quality assurance regimes and indeed the designers own colleagues. We then illustrate this model with a discussion of a new course development project: “Dealing with Drugs: Policy, Prevention and Practice.” This is a hard case which foregrounds each dimension of the model.